Association Between Andropause and Demographic Factors with Depression Among Police Officers In Bali - Depa, Yosep Ardian; Pramesemara, I Gusti Ngurah; Negara, I Made Oka; Wardana, I Nyoman Gede (Indonesian Andrology and Biomedical Journal, 2024)
Background : Andropause is a health problem in men caused by a decrease in free testosterone levels. Depression is a mental disorder that happens with a person that is related to mood.Objective : This research aims to determine the relationship between Andropause and Depression in police officers in Polda Bali in 2023. Methods : This research is a descriptive-analytical study with a cross-sectional study design. Andropause was assessed using the ADAM questionnaire, and depression was assessed using the PHQ- 9 questionnaire. The sample was selected using a purposive sampling technique. Results : There were 60 respondents in this study. A total of 31 people (51.7%) respondents were positive for Andropause, and 29 people (48.3%) were negative for Andropause. Meanwhile, 12 people (20.0%) of respondents experienced mild depression, and 48 people (80.0%) did not experience depression. Ten (10) respondents experienced Andropause with Depression. There is a significant relationship between Andropause and Depression (p=0.003). The odds ratio (OR 95% CI) obtained was 6.429 (1.270-32.541). Also there is a significant relationship between Stress and Depression with p<0,001 (0,000), with OR 21 (4,4-100,1) Conclusion : The majority of police officers in Polda Bali were found to experience Andropause and Depression, as many as 10 people (32.3%). As age increases, the incidence of Andropause increases, and in the respondent population, most of whom are in the mid-life crisis period, it increases the possibility of depression. Police officers in Polda Bali with Andropause have a 6.429 times greater risk of experiencing depression